Making expertise fit: On the use of certified versus experiential knowledge in becoming an informed patient. (May 2021) - Versteeg, Wytske; te Molder, Hedwig
This article reports a discursive psychological study of online conversations among patients with ADHD, diabetes, or ALS on what constitutes an "informed patient." Being informed means different things for different patient groups. Whether patients prioritize experiential or certified expert knowledge is not indicative of patients' preferences per se but depends on how they give meaning to the responsibilities particular to their disease. ADHD patients hold each other accountable for demonstrating the seriousness of their disease. ALS patients use expert information to orient to a norm of thinking positive. Diabetes patients challenge experts to carve out independence from the diabetes regimen.